PROTAGONIST’S ROUND CHARACTERS IN JOHN GREEN’S NOVEL PAPER TOWNS - Feyzar Azhari (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
This research was aimed at seeing the protagonist's characters portrayed in the novel Paper Towns by John Green. The research applied the theory of Flat and Round Character proposed by E. M. Forster (1993). This research follows qualitative descriptive method proposed by Creswell (2003), an effective model that occurs in a natural setting that enables the researcher to develop a level of detail from being highly involved in the actual experiences. The result of the analysis shows that the significant protagonist's characters in the novel are distinctive self-disclosure, great ambition and affection. All the distinctive characters drive the protagonist to break the string with the people around her and bring a conflict with her parents.